Physicians’ Attitudes Toward Adolescent Confidentiality Services: Scale Development and Validation - Jeremić Stojković, Vida (Zdr Varst, 2020)
INTRODUCTION: Confidentiality is one of the oldest ethical principles in healthcare. However, confidentiality in adolescent healthcare is not a universally-accepted doctrine among scholars. The ethical acceptability of confidential services in adolescents’ healthcare is based on perceptions of adolescent maturity and an appreciation of its importance to adolescents’ access and utilization of healthcare services. Despite legal policies that promote adolescents’ rights, physicians’ attitudes toward adolescent confidentiality can be a determining factor in their ultimate decision to protect adolescents’ confidentiality. METHOD: A new Attitude towards Adolescent Confidentiality Scale was developed based on the results of a qualitative interview study. This new instrument was administered to a sample of 152 physicians working at school pediatric and gynecology departments in 13 primary healthcare institutions in Belgrade. Principal component analysis was applied to determine the main components of the scale. Reliability was assessed by calculating Cronbach alpha and mean inter-item correlations. RESULTS: Psychometric analysis of the final 19-item version of the scale showed a high level of reliability (Cronbach alpha of 0.83). Principal component analysis showed four components, which present subscales of the instrument: Confidentiality in clinical situation, Iimportance of confidentiality, Adolescent maturity, and Communication with parents. CONCLUSIONS: The instrument showed satisfactory levels of reliability and validity. The results of the scale dissemination may be a valuable tool for needs assessment for future educational interventions and training programs that will raise physicians’ awareness of the importance of adolescent confidentiality.